The Influence of Regional Government Policy Implementation on the Effectiveness of Ketapanrame Trawas Tourism Village Development: Pengaruh Implementasi Kebijakan Pemerintah Daerah Terhadap Efektivitas Pengembangan Desa Wisata Ketapanrame Trawas - Sukmana, Hendra; Choiriyah, Ilmi Usrotin; Balahmar, Ahmad Riyadh Umar (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
The study was conducted with the aim of determining and analyzing the effect of local government policy implementation on the effectiveness of Ketapanrame Trawas tourism village development in Mojokerto Regency. The study was conducted using a quantitative approach with a causal associative research design. Data collection techniques were carried out using questionnaires involving employees of the Tourism Office, village officials, business actors, and tourists. The data were obtained and analyzed using simple linear regression. The results showed that the implementation had a significant effect on the effectiveness of the development of the Ketapanrame Trawas tourist village in Mojokerto Regency. The r-square value was below 50%, indicating that the policy implementation was not yet optimal in supporting the development of the Ketapaname Trawas tourist village in Mojokerto Regency